2015
DOI: 10.1038/srep09734
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature direct copper-to-copper bonding enabled by creep on (111) surfaces of nanotwinned Cu

Abstract: Direct Cu-to-Cu bonding was achieved at temperatures of 150–250 °C using a compressive stress of 100 psi (0.69 MPa) held for 10–60 min at 10−3 torr. The key controlling parameter for direct bonding is rapid surface diffusion on (111) surface of Cu. Instead of using (111) oriented single crystal of Cu, oriented (111) texture of extremely high degree, exceeding 90%, was fabricated using the oriented nano-twin Cu. The bonded interface between two (111) surfaces forms a twist-type grain boundary. If the grain boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(87 citation statements)
references
References 22 publications
0
77
0
Order By: Relevance
“…There were 5 voids in the nt-Cu joint and 12 in the polycrystalline Cu joint. It was reported that the surface diffusion of Cu on (111) planes is faster by 3–4 orders in magnitude than other major planes 17 , 18 . Therefore, the (111) surface facilitates the diffusion of Cu atoms and then voids in the bonding interface can be filled by the Cu atoms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 5 voids in the nt-Cu joint and 12 in the polycrystalline Cu joint. It was reported that the surface diffusion of Cu on (111) planes is faster by 3–4 orders in magnitude than other major planes 17 , 18 . Therefore, the (111) surface facilitates the diffusion of Cu atoms and then voids in the bonding interface can be filled by the Cu atoms.…”
Section: Resultsmentioning
confidence: 99%
“…(111) oriented and nanotwinned Cu (nt-Cu) has attracted much attention due to its high surface diffusivity on the (111) plane 17 , 18 . The rapid surface diffusion has enabled low-temperature direct bonding in the range of 150 to 200 °C under an ordinary vacuum of 10 −4 to 10 −3 torr.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Panigrahi et al demonstrated an optimized Cu rich metal-alloy (Manganin) passivation technique that not only helps in passivate the Cu surface but also inherently enhanced Cu (111) oriented plane at the interface which results in high quality reliable bonding at 140 C [52]. Besides, Liu et al proposed a novel surface modification technique to form nanotwinned Cu surface at the interface in order to enhance the diffusion capability during thermocompression cycle and subsequent bonding was performed at 150˚C with a nominal compressive stress of 0.69 MPa [53]. Also, microstructure behavior of the bonded Cu-Cu interface was examined using FIB imaging for different deposition conditions at different bonding conditions and different deposition conditions as shown in Fig.…”
Section: Cu-cu Bonding By Texturing Cu Crystal Orientationmentioning
confidence: 99%
“…(4) Recently, modified processes to enhance direct Cu bonding have been suggested. (5)(6)(7)(8)(9)(10)(11) Fujitsu Laboratories proposed a surface grain refining pretreatment, which combines diamond cutting, organic acid vapor, and vacuum ultraviolet treatments. (12,13) Diamond cutting is performed to acquire a fine crystal layer underneath the surface, and formic acid vapor removes Cu oxides on the cut surface.…”
Section: Introductionmentioning
confidence: 99%